2000
DOI: 10.1108/09564230010360164
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life and performance – An ad hoc investigation of two key elements in the service profit chain model

Abstract: Service profit chain is a well-received model to explain the sustainable competitiveness of many service organizations. The model attributes a service organization's financial and market performance to its relationships with its customers and employees. According to the service profit chain, internal service quality serves the foundation of the model and it ignites a chain effect leading to an organization's growth and profitability in the end. The purpose of this study is to provide an ad hoc analysis of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 25 publications
6
63
0
15
Order By: Relevance
“…In the same line of research, the studies of Yingzi et al (2005) in the Chinese insurance sector and Lau (2000), that explored the relationship between profitability and quality of life at work with data of 28 American service companies, confirm the results obtained in the present study referring to clusters 1 and 4, that, even having focused on profitability and not on the retention rate, confirmed the existence of the relation between customers and employees´ satisfaction.…”
Section: Cluster Analysessupporting
confidence: 88%
“…In the same line of research, the studies of Yingzi et al (2005) in the Chinese insurance sector and Lau (2000), that explored the relationship between profitability and quality of life at work with data of 28 American service companies, confirm the results obtained in the present study referring to clusters 1 and 4, that, even having focused on profitability and not on the retention rate, confirmed the existence of the relation between customers and employees´ satisfaction.…”
Section: Cluster Analysessupporting
confidence: 88%
“…Pay, satisfaction, and promotion opportunities also influence performance (Herzberg, 1966;Hallowell, Schlesinger & Zornitsky, 1996;Lau, 2000). Carlsen (2003) believes that a motivated workforce is essential, as the complete participation of employees will inevitably drive the profitability of the organization.…”
Section: Organisational Rewardsmentioning
confidence: 99%
“…Using samples from Standard & Poors 500 companies, Lau (2000) found that QWL companies have a higher growth rate as measured by the five-year trends of sales growth and asset growth. However, the outcome for profitability yield mixed results on Walton's (1974) conceptualisation of QWL.…”
Section: Past Research On Qwlmentioning
confidence: 99%